Radiocarbon bomb spike reveals biological effects of Antarctic climate change - Clarke, Laurence J; Robinson, Sharon A; Hua, Quan; Ayre, David J; Fink, David (Research Online, 2012)
The Antarctic has experienced major changes in temperature, wind speed and stratospheric ozone levels during thelast 50 years. However, until recently continental Antarctica appeared to be little impacted by climate warming, thusbiological changes were predicted to be relatively slow. Detecting the biological effects of Antarctic climate changehas been hindered by the paucity of long-term data sets, particularly for organisms that have been exposed to thesechanges throughout their lives. We show that radiocarbon signals are preserved along shoots of the dominant Antarcticmoss flora and use these to determine accurate growth rates over a period of several decades, allowing us toexplore the influence of environmental variables on growth and providing a dramatic demonstration of the effects ofclimate change. We have generated detailed 50-year growth records for Ceratodon purpureus and three other Antarcticmoss species using the 1960s radiocarbon bomb spike. Our growth rate and stable carbon isotope (d13C) data showthat C. purpureus¿ growth rates are correlated with key climatic variables, and furthermore that the observed effects ofclimate variation on growth are mediated through changes in water availability. Our results indicate the timing andbalance between warming, high-wind speeds and elevated UV fluxes may determine the fate of these mosses and theassociated communities that form oases of Antarctic biodiversity.